Plate waste of inpatients with diabetes mellitus - Rafisa, Anggun (International Journal Of Community Medicine And Public Health, 2020)
Background: The nutrition services of inpatient with diabetes mellitus is very important because dietary management is the key to controlling blood glucose level. Ensuring the patient to consume all the food served by the hospital or reduce the plate waste may help patients to meet their nutritional needs. This study aimed to investigate plate waste of inpatient with diabetes mellitus in hospitals and its contributing factors so the quality of food service in the hospital could be enhanced. Methods: The sample of the study was 22 inpatient with diabetes mellitus at Al Islam Hospital in Bandung, Indonesia from November 2014 to February 2015. The patient's plate waste at breakfast, lunch and dinner for 2 days was weighed using an electronic scale. Patients were also interviewed to find out the reasons for wasting food. Results: The overall mean of plate waste in this study was 13.26% of food served. Porridge was the type of food that had the highest mean percentage of plate waste (17.38%). Vegetables were the second-highest wasted food (17.05%). Loss of appetite, lack of knowledge, cold food temperature and large main plate portion were the reasons for food wastage. Conclusions: The type of food that wasted the most by inpatient with diabetes mellitus was porridge and vegetables. Improving the quality of food service and delivery as well as increasing the role of health workers to educate and encourage patients to eat while under treatment in hospitals are interventions that can be done to reduce the amount of inpatient plate waste.